A masked, placebo-controlled, randomized clinical trial evaluating safety and the effect on cardiac function of low-dose rapamycin in 17 healthy client-owned dogs - Barnett, Brian G.; Wesselowski, Sonya R.; Gordon, Sonya G.; Saunders, Ashley B.; Promislow, Daniel E. L.; Schwartz, Stephen M.; Chou, Lucy; Evans, Jeremy B.; Kaeberlein, Matt; Creevy, Kate E. (Frontiers in Veterinary Science, 2023)
Introduction: Geroscience studies of low-dose rapamycin in laboratory species have identified numerous benefits, including reversing age-related cardiac dysfunction. Cardiovascular benefits have been observed in dogs with 10 weeks of treatment, raising questions about possible benefits and adverse effects of long-term use of low-dose rapamycin. The objectives of this study were to assess the impact of 6 months of low-dose rapamycin on echocardiographic indices of cardiac function in healthy dogs and to document the occurrence of adverse events. Methods: Seventeen client-owned dogs aged 6–10 years, weighing 18–36 kg, and without significant systemic disease were included in a prospective, randomized, placebo-controlled, masked clinical trial. Low-dose rapamycin (0.025 mg/kg) or placebo was administered three times per week for 6 months. Baseline, 6-month, and 12-month evaluation included physical examination, cardiology examination, and clinicopathology. Three-month evaluation included physical examination and clinicopathology. Owners completed online questionnaires every 2 weeks. Results: There were no statistically significant differences in echocardiographic parameters between rapamycin and placebo groups at 6 or 12 months. No clinically significant adverse events occurred. In 26.8% of the bi-weekly surveys owners whose dogs received rapamycin reported perceived positive changes in behavior or health, compared to 8.1% in the placebo group (p = 0.04). Discussion: While no clinically significant change in cardiac function was observed in dogs treated with low-dose rapamycin, the drug was well-tolerated with no significant adverse events.